From the dual apprenticeship system to a dual labor market? The German high-skill equilibrium and the service economy - Werner Eichhorst; Paul Marx (Institute for the Study of Labor (IZA), 2009)
Different models of protection against labor market risks are associated with diverging models of economic performance. Historically established institutional complementarities between labor market regulation, unemployment protection, and vocational training tend to mirror specific national models of economic production. For example, the German dual apprenticeship system is a core feature of the corporatist model of diversified quality production. This, in turn, is supported via skills-protecting, earnings-related unemployment insurance, skills-oriented active labor market policies and strong dismissal protection so that long-term productive employment relationships become viable. The paper explores the connection between structural change and the development of skill creation in the German case with a particular focus on the difference between manufacturing and services as well as between different types of service sub-sectors. The paper takes manufacturing, a sector dominated by standard employment, as a reference point but mainly addresses different segments of the service economy: traditional ones (banking and insurance), new high-skill sectors (IT and the creative economy) and growing areas of low-skill services (hotels and restaurants, cleaning). We find that dynamic job creation in these segments of the service sector was possible due to a less regulated institutional environment.
urn:nbn:de:101:1-2009062212
Keywords: J31; J44; J24; 330; Service sector; Germany; dual labor market; low-skilled work; atypical employment; Dualer Arbeitsmarkt; Arbeitsmarktflexibilisierung; Kündigungsschutz; Facharbeiter; Arbeitsverhältnis; Ungeschützte Beschäftigung; Dienstleistungssektor; Beschäftigungseffekt; Strukturwandel; Drei-Sektoren-Hypothese; Deutschland